Post a New Question


posted by .

When you use the quadratic formula (x= -b+/=......) can you use that on equations like X^4+2X-8?

If not, how would you algebraically find the roots of: X^4+2X-8?


  • Math -

    no you may not.

    I do not know any easy way to do what you wish.

    If it were
    x^4 + 2 x^2 -8
    that would be easy
    let z = x^2
    z^2 + 2z - 8 = 0
    z = 2 or z = -4
    then x = +/- sqrt 2
    or x = +/- 2i

  • Math -

    You can't use the quadratic formula for such an equation. But you solve third and fourth degree equations algebraically and the way that is done uses a lot of the techniques that arise in case of quadratic equations.

    Solving a general fourth degree equation (one that doesn't have an obvious solution that you can find by attempting some trivial factorization) involves completing a square, just like in case of the derivation of the quadratic formula.

    In the case at hand, you can write:

    x^4 = -2x + 8

    If we can make both sides a perfect square, we can extract the square root. But the right hand side is not a perfect square. The left hand side is x^4 = (x^2)^2, and that is obviously a perfect square. The trick is then to add a parameter y inside the square so that as a function of y, it is always a perfect square:

    (x^2 + y)^2 = x^4 + 2 x^2 y + y^2

    Then the equation you want to solve implies that this is equal to:

    2 x^2 y - 2 x + y^2 + 8

    So, we have the equation:

    (x^2 + y)^2 = 2 y x^2 - 2 x + y^2 + 8

    Note that this equation is equivalent to the eqution you want to solve, no matter what you chose for y. So, the solution for x is not affected by y.

    Moreover, no matter what you chose for y, the left hand side is always a perfect square. What we then can do is to chose a special value for y such that the right hand side becomes a perfect square.

    Here what you've learned from solving quadratic equations can be used. The term inside the root of the quadratic equation (b^2 - 4 a c) is called the discriminant, if this is zero then the quadratic expression is a perfect square. So, we need to calculate the discriminant, equate that to zero and solve for y.

    We have:

    a = 2 y

    b = -2

    c = y^2 +8


    b^2 - 4 a c =

    4 - 8 y (y^2 + 8) =

    -8 y^3 -64 y + 4

    So, we first need to solve the equation:

    y^3 + 8 y - 1/2 = 0

    Let's skip this step and assume that we have the solution to this equation. Then you just plug that into the equation:

    (x^2 + y)^2 = 2 y x^2 - 2 x + y^2 + 8

    The right hand side is a perfect square, so we can write:

    2 y x^2 - 2 x + y^2 + 8 =

    2 y (x^2 - 1/y x + y/2 + 4/y) =

    2 y [x - 1/(2y)]^2

    So, we have:

    (x^2 + y)^2 = 2 y [x - 1/(2y)]^2

    Take square roots of bth sides:

    x^2 + y = ± sqrt(2y) (x + 1/(2y))

    And this is just an ordinary quadratic equation that you can solve using the quadratic formula! The ± sign means that there are two quadric equation, each has (in general) two solutions, so in general you get 4 solutions.

    The question then remains of how to solve that third degree equation for y:

    y^3 + 8 y - 1/2 = 0

    You can do this by writing:

    y^3 = -8 y + 1/2

    You can compare this to what you get when you expand out (a+b)^3:

    (a+b)^3 = a^3 + b^3 + 3 a^2b + 3 a b^2

    The right hand side can be written as:

    3 a b (a + b) + a^3 + b^3.

    So, we have the identity:

    (a+b)^3 = 3 a b (a + b) + a^3 + b^3.

    This is obviously always valid, no matter what a and b are. But this looks similar to the equation we want to solve:

    y^3 = -8 y + 1/2

    with y playing the role of a + b. Suppose then we somehow manage to find an a and b such that

    3 a b = -8


    a^3 + b^3 = 1/2

    Then because

    (a + b)^3 = 3 a b (a + b) + a^3 + b^3

    is always valid, it is also valid for this particular case. But then:

    (a + b)^3 = -8 (a + b) + 1/2

    which means that y = a + b then satisfies the equation we want to solve:

    y^3 = -8 y + 1/2

    Finding a and b, involves nothing more than solving a quadratic equation.

    Taking te third power of the equation

    3 a b = -8


    27 a^3 b^3 = - 512

    And we also have the equation:

    a^3 + b^3 = 1/2


    A = a^3

    B = b^3

    Then you have the equations:

    A B = -512/27

    A + B = 1/2

    If you use the last one to express B in terms of A and plug that into the first one, you obtain a quadratic equation for A.

    Then from A and B you compute a and b and then y is given as a + b.

    So, you see that solving third and fourth degree equations is easy, you only need to use same kind of algebra that goes into solving quadratic equations.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question